Dislipidemias y su incidencia en la pancreatitis aguda en pacientes de 20 -40 años ciudadela la salud cantón Quevedo provincia los Ríos primer semestre 2015 - Bonilla Zambrano, Jhon Ernesto (2015)
Dyslipidemias are disorders in which there is increased cholesterol, triglycerides, HDL, LDL, VLDL, in blood plasma. These diseases are classified as isolated or mixed pathologies can be genetic or environmental (diet, physical activity, obesity) cause. Acute pancreatitis is a potentially fatal disease if not detected gravity and time. The consequences of acute pancreatitis is determined by two factors that reflect the severity of the disease: pancreatic necrosis and organ failure. Acute pancreatitis occurs when defense mechanisms fail, allowing activation of precursor enzymes within the pancreas causing damage of the pancreas. In this study, tests were performed to 139 patients health sector had dyslipidemia above the normal value and subsequently presence of acute pancreatitis. KEYWORDS: Dyslipidemia, hypertriglyceridemia, acute pancreatitis.